1999
DOI: 10.1007/s005350050301
|View full text |Cite
|
Sign up to set email alerts
|

Association of cyclin D1 expression with factors correlated with tumor progression in human hepatocellular carcinoma

Abstract: The amplification and/or rearrangement of the cyclin D1 gene, a positive regulatory element of the G1 to S phase of the cell cycle, has been reported in various human tumors, suggesting an oncogenic role of this gene. In this study, we investigated the expression of cyclin D1 in the formalin-fixed and paraffin-embedded human hepatocellular carcinoma (HCC) tissues of 25 patients, using monoclonal antibody 5D4 raised against cyclin D1. Two distinct patterns of staining were observed in HCC cells, nuclear and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
27
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
7
27
0
1
Order By: Relevance
“…In pituitary (Hibberts et al, 1999;Simpson et al, 2001) and ovarian (Dhar et al, 1999) tumours, cytoplasmic cyclin D1 has been reported (35 and 59% of cyclin D1-positive cases, respectively) but no correlations were identified. In hepatocellular carcinomas, cytoplasmic cyclin D1 appeared to significantly correlate with prognostic factors like intrahepatic metastasis (Sato et al, 1999). A large study which assessed cyclin D1 localisation was performed with 150 transitional cell carcinomas of the bladder, wherein cytoplasmic cyclin D1 increased with disease progression and correlated with decreased survival (Tut et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In pituitary (Hibberts et al, 1999;Simpson et al, 2001) and ovarian (Dhar et al, 1999) tumours, cytoplasmic cyclin D1 has been reported (35 and 59% of cyclin D1-positive cases, respectively) but no correlations were identified. In hepatocellular carcinomas, cytoplasmic cyclin D1 appeared to significantly correlate with prognostic factors like intrahepatic metastasis (Sato et al, 1999). A large study which assessed cyclin D1 localisation was performed with 150 transitional cell carcinomas of the bladder, wherein cytoplasmic cyclin D1 increased with disease progression and correlated with decreased survival (Tut et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…HCC (37). Recent data suggest that HBx-mediated cyclin D1 up-regulation in mammary gland cells can induce tumors as well despite the differences between hepatocyte and mammary gland cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of our macroarray pattern did not result from individual genetic variations, since we compared tumour and non-tumour Hierarchical clustering and cDNA macroarray-based analyses allowed us to identify a number of potential gene networks which were deregulated in the context of liver carcinogenesis. Some of these genes, such as betacatenin, p53, TGF-beta and genes involved in G1/S transition, have previously been incriminated in HCC or the development of other cancers (Abou-Shady et al, 1999;Buendia, 2000;Ito et al, 1999;Sato et al, 1999;Vousden, 2000;Wong et al, 2001;Yuspa et al, 1994). In addition, our analysis has highlighted other regulatory pathways which may be of importance to our understanding of liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%